Garci-Tea: Inovasi Pengolahan Limbah Kulit Manggis menjadi Produk Teh di Desa Sagalaherang Kidul, Subang - Fadhillah, Muhamad Arya; Khairunnisa, Safira Firdaus; Azzahra, Aulia; Ramdani, Ridwan; Salsabila, Aisyah; Zahra, Namira Argya; Agustiani, Oka Hasana; Setiawan, Muhammad Rifki Ramdhani; Putra, Erianto Indra; Carolina, Anne (Jurnal Pusat Inovasi Masyarakat, 2024)
Sagalaherang Kidul Village has great potential in the utilization of mangosteen peel waste which has not been optimized. To utilize this potential, KKNT-I IPB students carried out community service activities aimed at processing mangosteen peel waste into Garci-Tea, a healthy tea innovation with high economic value. This counseling was aimed at women members of the Family Empowerment and Welfare Institution (PKK) and was held on July 28, 2024 at the house of the Head of Dusun 4 Krajan. Through this program, participants were taught about the economic potential of mangosteen peel, which is rich in antioxidants, and its easy and practical processing techniques. The program methods included training and hands-on demonstrations, starting from drying, grinding, and serving the tea. The results of the activities showed an increase in participants' knowledge and skills and provided opportunities to create products of economic value from agricultural waste. This activity is expected to improve community welfare and health and encourage more optimal utilization of local resources. This activity also emphasizes the importance of empowering women in developing skills that support family economic improvement.